AN ANALYSIS OF POLITENESS STRATEGIES USED BY ANIES BASWEDAN’S SPEECH ON METRO TV “GAGASAN UNTUK INDONESIA LEBIH BAIK” - Dwi Santoso; Nila Aulia (Ikatan Dosen Menulis, 2023)
Politeness strategies are ways that used by someone to convey her/his utterances politely. This study applied a qualitative descriptive approach. This study aims to examine the politeness strategies used by Anies Baswedan on Metro Tv. The source of data of this study was obtained from youtube. The collected data is assessed using Brown and Levinson's (1987). Politeness Strategies theory to find out the types of politeness strategy and its sub-strategies. After analyzing the data, the researchers concluded that there are four types of politeness strategies found in the speech on Metro Tv with the titel “Gagasan Untuk Indonesia Lebih Baik”